Examining digital influencers’ impact on customer's hedonic motivation, utilitarian motivation and purchase intention - Tanarto, Gabrille Maria Magdalena; Mujanandi, Yusuf Al-Islam Al; Manaf, Peri A. (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to investigate how external factors influence people's intentions to buy food online. A survey was conducted using an online form that was widely distributed to people who follow digital influencers on social media, have made online food purchases, and live in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi). The study was conducted to gather a more comprehensive view of consumer shopping behavior in Indonesia by combining trends, visual appeals, sales promotion, and information availability from digital influences in social media that impact customer motivation (hedonic and utilitarian) and customer purchase intention for food products online. The research results demonstrate a genuine relationship between digital influences and their impact on social networks as a new trend of the digital era. The study also proves that there is a positive relationship between the hedonistic motivation and the Utilitarian motivation on purchase intention. Moreover, the research shows that promotions carried out on different platforms from the sales platform can also have a significant impact on consumer motivation and purchasing intentions. Based on the research results, we recommend that food product sellers should consider using digital influences as promotional tools on social platforms. We recommend that future researchers investigate differences in shopping motivation based on different products or consumer market segments, especially in terms of external factors that trigger motivation to shop for food through digital activities.